Ta có:
\(\frac{a}{a'}+\frac{b'}{b}=1\)
\(\Rightarrow\frac{a}{a'}.\frac{b}{b'}+\frac{b'}{b}.\frac{b}{b'}=\frac{b}{b'}\)
\(\Rightarrow\frac{ab}{a'b'}+\frac{b'b}{bb'}=\frac{b}{b'}.\)
\(\Rightarrow\frac{ab}{a'b'}+1=\frac{b}{b'}\) (1).
Lại có:
\(\frac{b}{b'}+\frac{c'}{c}=1\)
\(\Rightarrow\frac{b}{b'}=1-\frac{c'}{c}\) (2).
Từ (1) và (2) \(\Rightarrow\frac{ab}{a'b'}+1=1-\frac{c'}{c}.\)
\(\Rightarrow\frac{ab}{a'b'}=-\frac{c'}{c}.\)
\(\Rightarrow abc=-a'b'c'\)
\(\Rightarrow abc+a'b'c'=0\left(đpcm\right).\)
Chúc bạn học tốt!